2016
DOI: 10.15386/cjmed-593
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome and the Quality of Life

Abstract: Background and aimsObstructive sleep apnea syndrome (OSA) affects the quality of life (QOL) due to the effects on the patient’s physical and mental function. QOL in sleep apnea may improve under continuous airway positive pressure (CPAP) therapy. The purpose of this study was to assess the OSA patients QOL before and after 3 months of CPAP therapy using Calgary Sleep Apnea Quality of Life Index (SAQLI).MethodsWe conducted a study in 79 sleep apnea subjects diagnosed using cardiorespiratory portable monitoring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
4
18
0
1
Order By: Relevance
“…22 Another study of 50 patients, predominantly men on CPAP for OSA, showed improvement in the sleep apnea QoL index 23 24 and sleep apnea QoL index. 25 A multicenter clinical effectiveness study showed improvement in FOSQ in all domains and similar to our study showed greater improvement in patients who were PAP adherent. 26 Our study differs from the existing clinical studies because it includes a robustly large number of patients and utilizes both sleep-related and global QoL instruments.…”
Section: Discussionsupporting
confidence: 88%
“…22 Another study of 50 patients, predominantly men on CPAP for OSA, showed improvement in the sleep apnea QoL index 23 24 and sleep apnea QoL index. 25 A multicenter clinical effectiveness study showed improvement in FOSQ in all domains and similar to our study showed greater improvement in patients who were PAP adherent. 26 Our study differs from the existing clinical studies because it includes a robustly large number of patients and utilizes both sleep-related and global QoL instruments.…”
Section: Discussionsupporting
confidence: 88%
“…2,14) Sleep apnea is closely related to quality of life because it induces daytime sleepiness and depressive mood. 15,16) In our study, we found that KOSA-18 scores were significantly reduced regardless of intracapsular or extracapsular tonsillectomy. It is consistent with the previous meta-analysis study.…”
Section: Discussionsupporting
confidence: 48%
“…Increased SF and decreased quality of sleep have an undesirable impact on QoL and wellbeing linked with EDS . The marked impairment of QoL in patients with OSA improved after 3 months of nCPAP treatment . Those with higher AHI and increased frequency of microarousal demonstrated better compliance and greater improvement in QoL with nCPAP therapy.…”
Section: Discussionmentioning
confidence: 98%
“…13 The marked impairment of QoL in patients with OSA improved after 3 months of nCPAP treatment. 14 Depressive symptoms have been shown to be reduced with nCPAP treatment in patients with severe strokes and sleep apnea. 15 An improvement in cognitive, visual, spatial, and verbal memory were observed after 3 months of The Health-Related QoL (HRQoL) in patients with Sleep Apnea Hypopnea Syndrome (SAHS) at the time of diagnosis was low.…”
Section: Discussionmentioning
confidence: 99%